Using Memristor Element to Improve the Reliability of Digital Circuits (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Memristor has been used as a filter stage to improve The reliability of digital circuits has been improved by using memristor. This element works as a filter stage to waive most of the glitches generated in prior stages. The proposed technique is applied to three different circuits to improve their reliability. Those circuits are: a chain of inverters represents a long path topology, c432 benchmark represents a short path circuit, c1908 benchmark represents a long path circuit. The memristor stage is connected between the last two stages of each output path of the circuit. The memristance of the memristor is changed using a certain parameter (x0), higher memristance means longer propagation delay and more glitches are attenuated. The experiment is run at different values of the memristance and the error probability is calculated at each value. The effect of this stage is studied by calculating the energy consumption and performance of the circuits with and without this stage. The Reliability-Energy-Performance trade-off relationship is found and introduced for each circuit, the results show that the reliability of the circuit is improved to the highest levels, when